CMTM7 shapes the chronic inflammatory and immunosuppressive tumor microenvironment in hepatocellular carcinoma as an M2 macrophage biomarker - Zhu, Zhipeng; Liu, Hanzhi; Fu, Huafeng; Luo, Yu; Chen, Baisheng; Wu, Xiaofang; Sun, Anran; Zhang, Fuxing; Wang, Tao (Scientific reports, 2024)
Transmembrane domain-containing 7 (CMTM7) is a protein located at the plasma membrane. It plays a role in regulating the development and immune microenvironment of tumor cells. However, the impact of CMTM7 on hepatocellular carcinoma (HCC) is not well understood. To better understand the role of CMTM7 in HCC, the correlations of CMTM7 with clinical characteristics, patient prognosis, chronic inflammation, and immune cell infiltration were analyzed using tissue microarray slides, sequencing datasets and various analysis tools (Web). The bulk sequencing analysis indicated that elevated expression of CMTM7 appears to promote chronic inflammation, immunosuppression, M2 macrophage infiltration, a diminished response to cancer immunotherapy, and an unfavorable clinical prognosis in patients with hepatocellular carcinoma (HCC). Further investigation through single-cell RNA sequencing and multiple fluorescence staining demonstrated that CMTM7 serves as a molecular marker for M2 macrophages and is associated with T cell exhaustion as well as highly plastic stem-like characteristics. We propose that CMTM7 may represent a novel immune checkpoint for HCC patients experiencing suboptimal therapeutic outcomes. Utilizing the Connectivity Map and AutoDock Vina, we predicted two potential compounds targeting CMTM7—fasudil and arachidonyltrifluoromethane—as promising therapeutic candidates. Collectively, these findings suggest that CMTM7-positive macrophages play significant roles in establishing an immunosuppressive tumor microenvironment while promoting highly plastic and stem-like traits in HCC cells, ultimately contributing to poor prognostic outcomes.